THE ANALYSIS OF GEN Z PURCHASE INTENTION ON TIK TOK LIVE STREAMING - Ajeng Aquinia; Kristina Anindita Hayuningtias; Bambang Sutejo; Lie Liana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The findings of this study offer valuable implications for marketers and businesses looking to optimize their strategies on TikTok. This emphasizes the need to harness the effect of celebrity to shape Gen Z’s purchase intention. The research explores the interplay between these variables, providing insight into the complexity of Gen Z’s decision-making process in the digital era and social media marketing. It also sheds light on the mechanism through which trust mediates the relationship between celebrity endorsement and purchase intention. Understanding the pivotal role of trust can guide the development and more effective and credible marketing campaigns in the realm of live-streaming TikTok. The respondents of this research were the Gen Z that live in Semarang. This research indicates that celebrity endorsement has a positive and significant effect on trust. Also, celebrity endorsement and trust have a positive and significant effect on purchase intention. Trust was found capable to mediate between celebrity endorsement and purchase intention.